2016
DOI: 10.1177/0887302x16664406
|View full text |Cite
|
Sign up to set email alerts
|

Body-to-Pattern Relationships in Women’s Trouser Drafting Methods

Abstract: The authors of this study explored (a) body-to-pattern measurement and shape relationships in trouser patterns drafted by two methods; (b) the consistency of these body-to-pattern relationships between methods and between differently shaped bodies within methods; (c) the patternmaking procedures that cause these outcomes; and (d) how these findings impact garment fit, particularly for mass customization. Body-to-pattern measurement and shape relationships were inconsistent between and within methods, making th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 25 publications
(46 reference statements)
0
42
0
Order By: Relevance
“…Currently pattern drafting remains a manual task often performed using one of a number of different methods. Analysis of pattern drafting methods has been undertaken to determine ease [7], understand theories incorporated into the process [5], and even to show how approaches can better recognise the individual size, shape, and proportions used in the process [6]. However there have been no studies focused on how body scanning technology directly informs existing methods of pattern drafting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently pattern drafting remains a manual task often performed using one of a number of different methods. Analysis of pattern drafting methods has been undertaken to determine ease [7], understand theories incorporated into the process [5], and even to show how approaches can better recognise the individual size, shape, and proportions used in the process [6]. However there have been no studies focused on how body scanning technology directly informs existing methods of pattern drafting.…”
Section: Introductionmentioning
confidence: 99%
“…However, the creation of Proceedings of 3DBODY.TECH 2017 8th International Conference and Exhibition on 3D Body Scanning and Processing Technologies, Montreal, Canada, 11-12 Oct. 2017 pattern blocks remains something almost exclusively done manually using 1D measurements, as has been the case from the start of the methods. Another factor which needs to be considered is the application of proportional rules during the draft process [1], [6], [15]. This is often used in place of actual measurements that may have historically been difficult to take.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, each recommends methods believed to be useful for shaping pattern to body in post-drafting garment fittings. [10] [11] [12] Furthermore, traditional pattern-drafting theory is inclusive of ease, making it difficult to isolate the pattern dimensions specifically required for body shape from that required for ease alone. [13] Pattern blocks are the base patterns from which all garments originate.…”
Section: Introductionmentioning
confidence: 99%
“…Most research has reported that using a specific pattern drafting method for different body shapes or sizes yields varied results [1]- [5]. This highlights the need for differently shaped garments to achieve good fit and the importance of developing a method of taking measurements and pattern construction methods to better reflect individuals or populations variability.…”
Section: Introductionmentioning
confidence: 99%